Using Blended Concessional Finance to Invest in Challenging Markets : Economic Considerations, Transparency, Governance, and Lessons of Experience - International Finance Corporation (International Finance Corporation, Washington, DC, 2021)
Blended concessional finance is the combination of concessional funds from development partners with commercial finance from development finance institutions (DFIs) and private sources. These resources can be used strategically to help mitigate risk in challenging emerging markets and attract private investment where it otherwise would not go. It can be an important source of finance to help reach the Sustainable Development Goals (SDGs) and address the economic challenges brought on by Coronavirus (COVID-19). This report examines IFC’s two decades of experience supporting pioneering projects with blended concessional finance. The report addresses issues such as why and when concessional finance is appropriate to support private sector projects; the key transparency, access, and governance processes required to implement projects efficiently and effectively; the principles for selecting and structuring projects; how to use blended concessional finance to invest in lower-income countries; and the different ways of structuring concessional finance facilities used by DFIs.